Novel surgical technique for macular holes with basal diameter >1000 μ - Debdulal Chakraborty; Soumen Mondal; Sabyasachi Sengupta; Subhendu Boral; Arnab Das (Taiwan Journal of Ophthalmology)
Closure rate of full-thickness macular holes (FTMHs) with basal diameter >1000 μ is known to be poor. Patients presenting with FTMH having a minimum basal diameter of >1000 μ without any coexistent retinal morbidity were offered vitrectomy, internal limiting membrane peeling, retinal massage, and aspiration of subretinal fluid from the MH. Visual acuity (VA) and spectral-domain optical coherence tomography (SD OCT) assessments were performed at baseline, week 1 after surgery and at postoperative months 1, 3, 6, and 12. VA, type of hole closure, presence of ellipsoid zone, and external limiting membrane defect were monitored. The primary endpoint was type 1 anatomical hole closure. Secondary outcome measure was a change in VA from baseline to 6-month follow-up and persistent hole closure at the final follow-up of 12 months. The mean age was 67.1 ± 9.1 years. Seven eyes were pseudophakic, and two underwent combined phacoemulsification with MH surgery. The mean minimum basal diameter of FTMH was 1162.4 ± 161 μ. The mean duration of visual loss was 11.3 ± 1.93 months. Type 1 closure of FTMH was seen in all patients on SD OCT, on the 7th postoperative day. The mean presenting VA was 1.06 ± 0.1 Logarithm of the minimum angle of resolution (logMAR). Best-corrected visual acuity improved to 0.91 ± 0.09 logMAR at 1-month follow-up (P = 0.005) (95% confidence interval [CI]: 0.061–0.251), 0.63 ± 0.1 logMAR (P < 0.001) (95% CI 0.339–0.527) at 3 months, and 0.55 ± 0.05 logMAR (P < 0.001) (95% CI 0.414–0.609) at 6 months. All holes were found closed at the final follow-up of 12 months. This novel technique can help achieve better outcomes and raise the primary anatomical success rate of FTMH with basal diameter >1000 μ.